The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1002/app.47281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanotubes decorated with silver nanoparticles as hybrid filler on properties of natural rubber nanocomposites

Abstract: Decoration of carbon nanotube (CNT) surfaces with silver nanoparticles (AgNPs) was performed using N,N‐dimethylformamide reducing agent. The CNT‐decorated with AgNP (CNT‐AgNP) was then used to prepare natural rubber (NR) nanocomposites via latex mixing method. Cure characteristics, mechano‐thermal relaxation, electrical conductivity, and thermal properties of the composites were investigated. It was found that the CNT‐AgNP gave cure properties improved over plain NR compounds in terms of scorch time, degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In addition, high thermal conductivity of GP might be another reason favoring the activation of ENR vulcanization. That is, high thermal conductivity of GP leads to higher rate of rubber vulcanization . In Figure , the GP‐activated ENR vulcanizate without stearic acid exhibited slightly lower crosslink density than the GP‐activated ENR vulcanizate with stearic acid.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, high thermal conductivity of GP might be another reason favoring the activation of ENR vulcanization. That is, high thermal conductivity of GP leads to higher rate of rubber vulcanization . In Figure , the GP‐activated ENR vulcanizate without stearic acid exhibited slightly lower crosslink density than the GP‐activated ENR vulcanizate with stearic acid.…”
Section: Resultsmentioning
confidence: 94%
“…The conductive NR composite with CNT-decorated AgNP (Figure 12) was prepared via the latex mixing method to get homogenous dispersion of the filler [42]. The decoration of CNT surfaces with AgNP significantly enhanced the electrical conductivity and lowered the percolation threshold concentration of NR composites when compared to the composites with plain CNT filler.…”
Section: Hybrid Carbon Nanotubes and Silver Nanoparticle In Natural Rmentioning
confidence: 99%
“…This might be due to the synergy of plasticizing by IL (BMI), contributed to good dispersion of CNT. It forms three-dimensional networks in the NR matrix [42].…”
Section: Hybrid Carbon Nanotubes and Ionic Liquid In Natural Rubber Cmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] As is well known, nanomaterials have often been added into polymer matrix to enhance its mechanical strength, friction and wear properties, due to their unique microstructure, surface and volume effects, and excellent physical and chemical properties. [7][8][9] For example, carbon nanotube (CNT), a tubular nanograde graphite crystal, has high elastic modulus, tensile strength, outstanding thermal, and tribological properties [10][11][12] and it is considered to be an ideal nanofiller for improving the mechanical properties and wear resistance of polymers. Johnson et al have reported that the total wear rate of high-density polyethylene (HDPE) is reduced by 50% and its friction coefficient is reduced by at least 12% by adding 5% CNT.…”
Section: Introductionmentioning
confidence: 99%